ANALISIS STILISTIKA TERHADAP DIKSI BERORIENTASI MORAL PADA NOVEL SARASWATI SI GADIS DALAM SUNYI KARYA A. A NAVIS SEBAGAI ALTERNATIF BAHAN AJAR BERMUATAN PENGUATAN PROFIL PELAJAR PANCASILA - Novia Nur Rizki; Panca Pertiwi Hidayati; Setiawan (STKIP Subang, 2023)
This research aims to find stylistic aspects and moral-oriented diction contained in the novel Saraswati Si Gadis Dalam Sunyi by A. A Navis, by analyzing and utilizing the results of the analysis as an alternative to the preparation of teaching materials for class XII SMA students. The method used in this research is descriptive qualitative research method. Descriptive qualitative research is research that puts forward interpretations in descriptive form. According to Sugiono (2011, pp. 8-9) in qualitative research the researcher acts as a key instrument and data collection techniques in this research are triangulated, the data analysis is inductive, and the research results emphasize the interpretation of generalizations. The data sources in this analysis are the novel Saraswati Si Gadis Dalam Sunyi by A. A Navis and several research support books. The results of the analysis of the novel related to stylistic aspects are as follows, 41 data on grammatical stylistic aspects of declarative sentence types, 14 data on figurative language of metaphor, 4 data on simile, 7 data on personification and 1 data on symbolism. In moral aspects, there are 3 data of moral aspects in the life of man and God, 41 data of moral aspects in life between man and man, and 20 data of moral aspects in life between man and his conscience. In diction, there are 14 data of connotative moral-oriented diction and 53 data of denotative moral-oriented diction. Then, the results of the analysis can be used as an alternative reference for teaching materials in learning Indonesian Language class XII in SMA.